DEVELOPMENT OF BINARY AND TERNARY COMPLEX OF CEFUROXIME AXETIL WITH CYCLODEXTRIN FOR IMPROVING PHARMACEUTICAL CHARACTERISTICS - KAUSHIK, SAKSHI; VERMA, RAVINDER; PUROHIT, DEEPIKA; PANDEY, PARIJAT; KUMAR, MANISH; KUMARI, BEENA; KAUSHIK, DEEPAK (International Journal of Applied Pharmaceutics, 2020)
Objective: The current research objective is systematic development and characterization of binary and ternary inclusion complexes of cefuroxime axetil with β-cyclodextrin to improve its pharmaceutical characteristics by using the kneading method. Methods: Phase solubility study was carried out using Higuchi and Connors method. Based on its result, binary complexes of cefuroxime axetil with different ratio of β-cyclodextrin were developed and characterized using differential scanning calorimeter (DSC), fourier transform infrared spectroscopy (FT-IR) and X-ray powder diffractometry (XRD). Then, binary complexes were analyzed for in vitro dissolution testing. The ternary complexes were developed using different ratio of PVP K-30 as a ternary component and evaluated for in vitro dissolution testing and in vitro taste masking. Results: Binary complex of cefuroxime axetil with β-cyclodextrin (1:1) showed better drug release than pure drug. During the development of the ternary complex, β-cyclodextrin (1:1) and 1% w/v PVP K-30 as a ternary agent resulted in an optimized ternary complex. The DSC, FT-IR and XRD studies clearly revealed the formation of binary and ternary complexes. The ternary complex showed better drug release of>85% within 30 min. in comparison to binary complex. The in vitro taste-masking study revealed the taste masking efficiency of the ternary complex of cefuroxime with β-cyclodextrin. Conclusion: The developed binary and ternary complex of cefuroxime axetil based on β-cyclodextrin with PVP K-30 showed improved in vitro dissolution rate and taste masking in comparison to pure drug. The drug release was better in ternary complexes. The present research work successfully shows the utility of binary and ternary complexes for improving pharmaceutical characteristics of cefuroxime axetil.